2017
DOI: 10.1007/s12250-016-3930-2
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular detection of viruses in Kenyan bats and discovery of novel astroviruses, caliciviruses and rotaviruses

Abstract: This is the first country-wide surveillance of bat-borne viruses in Kenya spanning from 2012-2015 covering sites perceived to have medium to high level bat-human interaction. The objective of this surveillance study was to apply a non-invasive approach using fresh feces to detect viruses circulating within the diverse species of Kenyan bats. We screened for both DNA and RNA viruses; specifically, astroviruses (AstVs), adenoviruses (ADVs), caliciviruses (CalVs), coronaviruses (CoVs), flaviviruses, filoviruses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 53 publications
5
53
1
1
Order By: Relevance
“…These bats were shown to harbor divergent viruses, including members of the families Astroviridae, Circoviruidae, Parvoviridae, Partitviridae, Coronaviridae, Picobirnavirdae, Adenoviridae, Herpesviridae, Papillomaviridae, Phenuiviridae, and Picornaviridae [98,99]. These recent studies build upon previous work [100][101][102][103] to further expand the diversity of the bat virome. Uniquely, the picobirnaviruses identified utilize an alternative genetic code [98].…”
Section: Other Virusesmentioning
confidence: 66%
“…These bats were shown to harbor divergent viruses, including members of the families Astroviridae, Circoviruidae, Parvoviridae, Partitviridae, Coronaviridae, Picobirnavirdae, Adenoviridae, Herpesviridae, Papillomaviridae, Phenuiviridae, and Picornaviridae [98,99]. These recent studies build upon previous work [100][101][102][103] to further expand the diversity of the bat virome. Uniquely, the picobirnaviruses identified utilize an alternative genetic code [98].…”
Section: Other Virusesmentioning
confidence: 66%
“…However, the genetically close relationships of the VP7, VP4, VP6, NSP3 and NSP5 gene segments of the study strain to bat strain 3081/BRA and/or bat-like human strain Ecu534, suggest that RVA/Human-wt/SUR/2014735512/2013/G20P[28] is of bat origin. A few investigators have reported the detection of human RVAs genes in bat RVA strains (Esona et al, 2010; Sasaki et al, 2016; Waruhiu et al, 2017), but this report represents only the second time bat RVAs gene segments have been found in a human RVA strain (Solberg et al, 2009). …”
Section: Resultsmentioning
confidence: 94%
“…Several improvements in viral detection and characterization methodologies such as high-throughput next generation sequencing have led to a successful discovery and characterization of several novel viruses in bats, including enteric pathogens such as RVA (Luis et al, 2013; Waruhiu et al, 2017). However, since the first detection and characterization of a human-bat reassortant RVA from a Straw-colored Fruit bat in 2010 (Esona et al, 2010), a few of other bat RVA strains, detected and characterized from different bat species and different geographic locations have been reported (Asano et al, 2016; He et al, 2013; Sasaki et al, 2016; Waruhiu et al, 2017; Xia et al, 2013; Yinda et al, 2016). Among the reported bat RVA strains, only bat RVA strain 3081/BRA from Brazil was closely related in the VP7, NSP3 and NSP5 gene segments with the study strain from Suriname.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last fifteen years, two Beta-CoVs, SARS-CoV and MERS-CoV, have jumped from bats to a mammalian intermediate host to humans (Field, 2009;Omrani et al, 2015). In addition, strains related to human Alpha-CoVs (HuCoV-229E, HuCoV-NL63) have been detected in bats, indicating the importance of the bat as a CoV reservoir (Pfefferle et al, 2009;Corman et al, 2015;Tao et al, 2017;Waruhiu et al, 2017). In this study, we characterized two Alpha-CoVs from Italian bats divergent from human CoVs strains and two new Alpha-CoV species.…”
Section: Discussionmentioning
confidence: 99%